Análise do Espaço Político Discricionário à disposição dos gestores públicos municipais paranaenses a partir da vigência do Novo Regime Fiscal sob a ótica da Teoria da Escolha Pública - Schiavo, Priscila dos Santos (2021)
Public Choice Theory (TEP) focuses on the behavior of individuals related to the entire political process, seeking to understand how government decisions are carried out; identify flaws in the political system, such as the self-interest of certain groups to the detriment of others; propose ways to limit these failures and efficiently establish the terms of trade between the State and individuals. It appears from the theory that there are factors associated with the political system that exert effects on the choices of public managers, such as the budget political cycle, the manager's political ideology and his political alignment with managers from other higher levels of government. Other factors such as budget rigidity; the scarcity of own resources followed by dependence on intergovernmental financial resources; the level of income of the municipality and the level of indebtedness may also be associated with the restriction of the capacity for discretionary choices on the part of municipal public managers. Thus, this study aimed to analyze the possible effects of political factors, together with financial-budgetary and socioeconomic factors, on the budgetary decision-making process of the municipalities of Paraná, using as a proxy for the decision-making process, the construct Political Discretionary Space (EPD), defined as the number of financial resources available to public managers to make their discretionary choices. Allied to this, a recent regulatory interference in the federal budget system was the New Fiscal Regime (NRF), established by Constitutional Amendment No. 95 of 2016 (EC No. 95/2016) and given the opportunity to test the possible effects of this regime on the municipal decision-making process, this study also intended to analyze whether the EPD was somehow impacted by the New Fiscal Regime. To achieve these goals, the EPD of 256 municipalities in Paraná was measured in the period from 2013 to 2019 and a panel data model by fixed effects was estimated to verify the variables that have effects on the EPD, and for further analysis, they were performed tests of correlations and tests of means. The results allow us to infer that the level of indebtedness; the degree of intergovernmental dependence; the number of inhabitants; the level of income and budgetary rigidity, verified by the commitment of revenues with personnel expenses and charges and with the mandatory constitutional expenses in the areas of health and education, exert significant effects on the behavior of the EPD. However, it was not possible to verify that the periods of municipal elections; the periods of state and federal elections; political ideology; political alignment with other governments; the budget surplus and investment expenditures were significant on the EPD. Based on the findings, it can be inferred that even indirectly, the validity of the NRF resulted in an increase in the EPD available to the analyzed municipal public managers. Other findings were that during the period of validity of the NRF there was an increase in the level of income and budgetary rigidity with regard to the commitment of revenues with expenditure on personnel and charges, in addition, there was a reduction in the degree of intergovernmental and in the surplus of municipalities. However, it was not possible to observe differences in the level of indebtedness, in public investments and in the commitment of revenues to the areas of health and education, in the municipal budgets analyzed under the NRF. The evidence found here contributes to society, as a way of controlling and monitoring the management of public resources in the analyzed municipalities; for public managers and public policy makers, as it sought to provide updated information to support decision-making in relation to possible influencing factors in the decision-making process and the budgetary impacts of the New Fiscal Regime at the municipal level. It brings contributions to public accounting and Public ChoiceTheory, noting that financial-budgetary, socioeconomic factors and the NRF influence the EPD, however, in this study, no significant associations were evidenced between the political factors, deduced from the TEP, on the behavior of the EPD, and it is necessary to better understand how this reality can be associated with the manager's behavior. It is suggested as future steps to deepen the results related to the political aspects and implications of the NRF on budgets, the identification of new variables that influence the decision-making process and an analysis in federal institutions, in order to verify if there was an impact of the NRF on their budgets.